N-body potentials in simulation of point defect properties - Chirkov, Andrey; Nazarov, Andrei (Diffusion Fundamentals, 2005)
This work is devoted to simulation of the diffusion features of point defects in bcc metals. The properties of point defects have been investigated with the usage of many-body interatomic potentials. This approach, based on the density-functional theory, permitted us to derive more adequate diffusion features of solids. The investigation is carried out within the framework of the Finnis-Sinclair formalism, developed for an assembly of N atoms and represents the second-moment approximation of the tight-binding theory. We used a new model, based on the molecular static method for simulating the atomic structure near the defect and vacancy migration in pure metals. This approach gives the opportunity to simulate the formation and the migration volumes of the point defects, taking into consideration the influence of pressure on structure and consequently on energy. The diffusion characteristics of bcc α-Fe and anomalous β-Zr have been simulated. The preliminary results of this research were presented and taken for publishing on the international conference “Diffusion in solids” (DiSo-2005) in May 2005.